How tough are you?

Find the sum of all positive integers r r such that for all primes p p where p > 500 p > 500 , S ( p r ) p r = 992 S(pr)-pr=992 , where S ( n ) S(n) is the aliquot sum or sum of all divisors of n n less than n n .


The answer is 496.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Dec 6, 2015

If σ ( n ) \sigma(n) is the sum of all divisors of n n , we want to find integers r r such that σ ( p r ) = 2 p r + 992 \sigma(pr) = 2pr + 992 for all primes p p greater than 500 500 . If r r is such a number then, by choosing p p large enough, we can assume that p p and r r are coprime. Since σ \sigma is a multiplicative function, it follows that ( p + 1 ) σ ( r ) = σ ( p ) σ ( r ) = σ ( p r ) = 2 p r + 992 (p+1)\sigma(r) \; = \; \sigma(p)\sigma(r) \; = \; \sigma(pr) \; = \; 2pr + 992 and hence p ( σ ( r ) 2 r ) = 992 σ ( r ) . p(\sigma(r) - 2r) \; = \; 992 - \sigma(r) \;. Since this identity must be true for all large enough p p , and so certainly for p p greater than 992 σ ( r ) |992 - \sigma(r)| , we deduce that σ ( r ) 2 r = 0 \sigma(r) - 2r = 0 and 992 σ ( r ) = 0 992 - \sigma(r) = 0 . Since 496 496 is perfect, r = 496 r=496 is the only solution of these equations, and so is such that σ ( p r ) = 2 p r + 992 \sigma(pr) = 2pr + 992 for all primes p p coprime to r = 496 r=496 .

Since any prime p p greater than 500 500 must be coprime to 496 496 , we see that 496 496 does indeed satisfy the equation, and so is the only solution. The sum of all solutions is, therefore, 496 496 .

Manuel Kahayon
Dec 5, 2015

Let r 1 , r 2 , r 3 r_1, r_2, r_3 \ldots be the factors of r r less than r r . Since p p is prime,

S ( r p ) = r 1 p + r 2 p + r 3 p + + r + r 1 + r 2 + r 3 + S(rp)=r_1p+r_2p+r_3p+ \ldots +r+r_1+r_2+r_3+ \ldots

S ( r p ) r p = ( r 1 p + r 2 p + r 3 p + r p ) + ( r + r 1 + r 2 + r 3 + ) S(rp)-rp=(r_1p+r_2p+r_3p+ \ldots -rp) +(r+r_1+r_2+r_3+ \ldots)

S ( r p ) r p = p ( r 1 + r 2 + r 3 + r ) + ( r + r 1 + r 2 + r 3 + ) S(rp)-rp=p(r_1+r_2+r_3+ \ldots -r) +(r+r_1+r_2+r_3+ \ldots)

This gives us r 1 + r 2 + r 3 + = r r_1+r_2+r_3+ \ldots =r

Therefore, S ( r p ) r p = p ( ( r 1 + r 2 + r 3 + ) r ) + ( r + r 1 + r 2 + r 3 + ) S(rp)-rp=p((r_1+r_2+r_3+ \ldots) -r) +(r+r_1+r_2+r_3+ \ldots)

S ( r p ) r p = p ( r r ) + ( r + r 1 + r 2 + r 3 + ) S(rp)-rp=p(r-r) +(r+r_1+r_2+r_3+ \ldots)

S ( r p ) r p = ( r + ( r 1 + r 2 + r 3 + ) ) S(rp)-rp=(r+(r_1+r_2+r_3+ \ldots))

S ( r p ) r p = r + r S(rp)-rp=r+r

S ( r p ) r p = 2 r S(rp)-rp=2r

992 = 2 r 992=2r

r = 496 r=496

Your argument does not work if r r and p p have a factor in common. Suppose, for example, that r = p 2 r = p^2 . Then r 1 , r 2 r_1,r_2 are 1 , p 1,p and so S ( r p ) = S ( p 3 ) = 1 + p + p 2 S(rp) \; = \; S(p^3) \; = \; 1 + p + p^2 while r 1 p + r 2 p + r + r 1 + r 2 = p + p 2 + p 2 + 1 + p = 1 + 2 p + 2 p 2 . r_1p + r_2p + r + r_1 + r_2 \; = \; p + p^2 + p^2 + 1+ p \; = \; 1 + 2p + 2p^2 \;.

Mark Hennings - 5 years, 6 months ago

Log in to reply

Thanks for the correction. :)

Manuel Kahayon - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...